Mink S38G Gene Polymorphism and Atrial Fibrillation in the Chinese Population: A Meta-Analysis of 1871 Participants - Yan-yan Li; Lian-sheng Wang; Xin-zheng Lu (The Scientific World Journal)
Mink gene S38G polymorphism in the β-subunit of slow activating component of the delayed rectifier potassium channel current potassium channel has been associated with increased atrial fibrillation (AF) risk. However, the individual studies results were still controversial. To investigate the association of Mink S38G gene polymorphisms with AF, a meta-analysis including 1871 subjects from six individual studies was conducted. Mink S38G gene polymorphism was significantly related to AF under allelic (OR: 1.380, 95% CI: 1.200–1.600, P<0.00001), recessive (OR: 1.193, 95% CI: 1.033–1.377, P=0.017), dominant (OR: 1.057, 95% CI: 1.025–1.089, P<0.00001), additive (OR: 1.105, 95% CI: 1.036–1.178, P=0.002), homozygous (OR: 1.128, 95% CI: 1.068–1.191, P<0.00001), and heterozygous genetic models (OR: 1.078, 95% CI: 1.014–1.146, P=0.016). A significant association between Mink S38G gene polymorphism and AF risk was found. G allele carriers may predispose to AF.